The End of 'Responsible Gambling': Reinvigorating Gambling Studies - Livingstone, Charles (Critical gambling studies, 2023)
This paper argues that gambling research has, since the neoliberal-inspired period of gambling legalisation in the late twentieth century, been dominated by a specific discourse, that of ‘responsible gambling’. This discourse originated in a conjunction of rationalities of government and capital, in the process of which commercial gambling was legitimated. Its liberalisation represented an extension of rationalities and technologies to form a new market from what had previously been an unlawful activity. The problems and harms associated with this liberalisation became subject to claims from some pockets of expertise, notably psy-sciences, and thus became a focus for analysis. As a consequence, gambling research has been characterised by a discourse of individual pathology as the focus of study. The orthodoxy formed from this discourse constitutes a system or apparatus of economic and quasi-medical power, in which reflexive relations between gambling operators, governments, charities, and some researchers, have been significant. These reflexive relations have largely constituted the field of gambling research. This paper contends that the orthodoxy of gambling research has failed to prevent harm arising from gambling and has restricted the expansion of knowledge. A systemic critique of the orthodox discourses and technologies that constitute much of gambling research is required to address these categories. This would also address a lack of diversity in theoretical framings of gambling research priorities. Alternative ways of conceptualising the problem of legalised gambling have emerged, most clearly under the discourse of ‘public health’. The current competition between these two discourses might be categorised as between an orthodoxy (‘responsible gambling’) and a heterodoxy (‘public health’). Extending the heterodoxy into a critical public health discourse may provide a basis for rapid expansion and diversification of the research field, particularly along paths that expand knowledge, facilitate effective regulation of harmful products, and prevent harm to individuals, communities, and populations.